Polymer-based thermal conductive composite material based on liquid metal interface bridging and multi-dimensional filler synergistic construction and preparation method thereof

CN122978701APending Publication Date: 2026-10-27SICHUAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611424977.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-15
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

同时,填料间如果只是机械结合而非化学键合,声子耦合弱,传热也会受阻

Benefits of technology

[0050]1、本发明提供了一种基于液态金属界面桥接与多维填料协同构筑的聚合物基导热复合材料及其制备方法,揭示了高填充体系下聚多巴胺包覆程度对复合材料导热性能“促进-阻碍”双向竞争的影响规律,明确了约3 h的最优氧化自聚合反应时间窗口,在改善界面相容性的同时避免了过厚聚多巴胺热阻层的负面效应,为聚多巴胺仿生界面改性在高填充导热复合材料中的应用提供了实验依据与工艺参考。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978701A_ABST
    Figure CN122978701A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of heat-conducting functional polymer-based composite materials, and particularly relates to a polymer-based heat-conducting composite material based on liquid metal interface bridging and multi-dimensional filler synergistic construction and a preparation method thereof. The application uses two-dimensional sheet-shaped aluminum powder coated by controllable polydopamine modification as a high-filling heat-conducting filler, uses eutectic gallium-indium liquid metal droplets chemically grafted by a silane coupling agent as a zero-dimensional flexible bridging filler to fill the gap between the two-dimensional sheet-shaped aluminum powder and the polymer matrix skeleton, and further adds one-dimensional heat-conducting carbon fillers to interpenetrate and lap between the two-dimensional sheet-shaped aluminum powder layers and the modified eutectic gallium-indium liquid metal droplet gaps. Through the above synergistic construction, a significant synergistic effect is generated under a specific component ratio, a three-dimensional hybrid heat-conducting network is constructed in the polymer matrix, the multi-phase interface thermal resistance is significantly reduced, the thermal conductivity of the composite material is greatly improved, and excellent mechanical properties and flexibility are simultaneously achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of thermally conductive functional polymer-based composite materials technology, specifically relating to a polymer-based thermally conductive composite material based on liquid metal interface bridging and multidimensional filler synergistic construction and its preparation method. Background Technology

[0002] With the rapid development of 5G mobile communication technology, artificial intelligence chips, new energy vehicle power batteries, and flexible wearable electronic devices, the power density of electronic components is increasing dramatically, leading to a significant increase in heat flux density. Inadequate thermal management will cause heat to accumulate inside devices, resulting in thermal failure, performance degradation, and even safety hazards. Therefore, developing thermal management materials and thermal interface materials that combine high thermal conductivity, excellent mechanical properties, and good flexibility has become a key technical challenge that urgently needs to be solved in the field of electronic packaging and thermal management.

[0003] Polymer-based thermally conductive composites are considered an ideal alternative to traditional metal and ceramic heat dissipation materials due to their advantages such as light weight, corrosion resistance, and ease of processing. However, polymers have low intrinsic thermal conductivity, necessitating the addition of high thermal conductivity fillers to construct a continuous thermally conductive network to improve the composite's thermal conductivity. Currently, metal fillers (such as aluminum, copper, and silver) and carbon-based fillers (such as graphene and carbon nanotubes) have attracted considerable attention due to their high intrinsic thermal conductivity. However, polymer / metal / carbon-based filler systems face the following common bottlenecks:

[0004] I. Significant Interfacial Thermal Resistance: Metal fillers generally have a dense oxide layer (such as Al2O3) on their surface, and carbon-based fillers exhibit poor compatibility with both the polymer matrix and the metal filler. Heat is primarily transferred via phonons (lattice vibrations) in polymer and carbon materials, while in metals it is transferred via a combination of free electrons and phonons. When heat crosses heterogeneous interfaces, due to the mismatch in vibrational density and modulus between the two materials, weak interfacial bonding, and the presence of micropores at the interface, heat carriers (phonons / electrons) are violently scattered at the interface, resulting in significant interfacial thermal resistance. Furthermore, if the fillers are only mechanically bonded rather than chemically bonded, phonon coupling is weak, further hindering heat transfer. These factors severely restrict the improvement of the thermal conductivity of composite materials.

[0005] 2. Incomplete thermal conductivity network: Rigid sheet-like metal fillers are difficult to fully overlap in the polymer matrix. There are a large number of non-contact areas between the fillers, which are occupied by the polymer matrix (e.g., the intrinsic thermal conductivity of aramid nanofibers is about 4.2 W / (m·K)) or even air micro-gaps (thermal conductivity is about 0.026 W / m·K). The heat flow channels in the point contact areas between the fillers are narrow, and an efficient three-dimensional thermal conductivity network cannot be formed.

[0006] To address the aforementioned issues, existing technologies primarily focus on improvements in two aspects: surface modification of the packing material and synergistic effects of multidimensional packing materials.

[0007] In terms of surface modification, polydopamine (PDA) biomimetic surface modification can form a strong adhesion layer on the surface of almost all kinds of materials (Haeshin Lee et al., Mussel-Inspired Surface Chemistry for Multifunctional oatings. Science 318, 426-430 (2007). DOI: 10.1126 / science.1147241), and has been widely used to improve the dispersibility and interfacial compatibility of thermally conductive fillers. Previous studies have shown that the catechol and amine groups contained in the PDA layer can form hydrogen bonds and other interfacial interactions with the polymer matrix, enhancing the interfacial bonding between the filler and the matrix, reducing interfacial gaps, thereby suppressing phonon scattering at the filler-matrix interface and reducing interfacial thermal resistance. However, it is important to note that PDA has a low intrinsic thermal conductivity (less than 1 W / m·K). While the PDA layer plays a role in interfacial compatibility, it also constitutes additional thermal resistance in series with the thermal conduction path. Only when the PDA coating amount is within an appropriate range are these two effects balanced; excessive coating amount increases the interfacial thermal resistance. However, existing research has primarily focused on boron nitride, graphite, and other ceramic or carbon-based fillers, as well as low-to-medium filler systems. For sheet-like metal filler systems with high filler volume fractions, the filler particles overlap significantly. The dominant limiting factor for the thermal conductivity of the composite material shifts from the filler-matrix interfacial thermal resistance to the filler-filler contact thermal resistance. The hindering effect of the low thermal conductivity PDA layer located at the filler overlap on heat conduction is further amplified. The influence of the PDA coating degree on the thermal conductivity of such high-filler systems still requires systematic research.

[0008] In terms of multi-scale filler synergy, existing technologies mostly focus on the synergistic construction of two-dimensional sheet-like metal filler systems with fillers of other dimensions. For example, one-dimensional carbon nanotubes have high aspect ratio and high intrinsic thermal conductivity, which can be interlaced and bridged between sheet-like filler layers. However, there are still large gaps between carbon nanotubes and metal fillers, resulting in interfacial thermal resistance. When used alone, they have limited efficiency in enhancing the thermal conductivity of highly filled metal systems. Summary of the Invention

[0009] To address the problems of the prior art, this invention provides a polymer-based thermally conductive composite material and its preparation method based on the synergistic construction of liquid metal interface bridging and multidimensional fillers. On one hand, this invention uses two-dimensional sheet-like aluminum powder controlled-coating with polydopamine (PDA) as a highly filled thermally conductive filler to enhance the interfacial bonding force of the sheet-like aluminum powder and suppress interfacial phonon scattering caused by its surface oxide layer. On the other hand, eutectic gallium-indium liquid metal microdroplets chemically grafted with silane coupling agent are used as zero-dimensional flexible bridging fillers to fill the gaps between the two-dimensional sheet-like aluminum powder and the polymer matrix framework. Furthermore, one-dimensional thermally conductive carbon-based fillers are added, interpenetrating and overlapping between the two-dimensional sheet-like aluminum powder layers and the gaps between the modified eutectic gallium-indium liquid metal microdroplets. Through this synergistic construction, a significant synergistic effect is generated under specific component ratios, constructing a three-dimensional hybrid thermally conductive network within the polymer matrix, significantly reducing the multiphase interfacial thermal resistance, and achieving a substantial improvement in the thermal conductivity of the composite material while maintaining excellent mechanical properties and flexibility.

[0010] To achieve the above objectives, the present invention employs a technical solution consisting of the following technical measures.

[0011] This invention provides a polymer-based thermally conductive composite material constructed synergistically from liquid metal interface bridging and multidimensional fillers. The raw materials comprise the following components by weight:

[0012] 40-70 parts of polymer matrix,

[0013] 120-160 parts of polydopamine-coated modified two-dimensional flake aluminum powder

[0014] 60-80 parts of modified eutectic gallium indium liquid metal microdroplets,

[0015] 7-12 parts of one-dimensional thermally conductive carbon-based filler;

[0016] The polydopamine-coated modified two-dimensional sheet aluminum powder is prepared by dispersing the two-dimensional sheet aluminum powder in a solution containing dopamine and then subjecting it to an oxidative self-polymerization reaction for 2.5 to 3.5 hours.

[0017] The modified eutectic gallium-indium liquid metal microdroplets are prepared by dispersing a eutectic gallium-indium alloy and a silane coupling agent in a solvent and then modifying the surface coordination.

[0018] In this document, the polymer matrix is ​​a conventional polymer material that is suitable for thermoforming in the art, such as either aramid nanofibers or cellulose nanofibers.

[0019] In one preferred embodiment, the polymer matrix is ​​aramid nanofibers, whose abundant amide bonds can form a hydrogen bond network with the polydopamine coating layer and the hydroxyl groups on the filler surface, which is beneficial for constructing a composite material skeleton with strong interfacial bonding. Typically, the aramid nanofibers can be prepared from aramid fibers using a deprotonation method.

[0020] To better illustrate the present invention and provide a specific technical solution, the polymer matrix is ​​aramid nanofibers. The preparation method of the aramid nanofibers is as follows: 1 g of aramid fiber, 1.5 g of KOH, and 20 ml of deionized water are added to 500 mL of dimethyl sulfoxide and mixed to obtain an ANF / DMSO dispersion. 100 mL of the ANF / DMSO dispersion is mixed with 200 mL of deionized water and stirred. Then, the mixture is vacuum filtered and washed to remove dimethyl sulfoxide and KOH, yielding an aramid nanofiber colloid. For convenient direct use, anhydrous ethanol can be added to prepare an aramid nanofiber / ethanol dispersion with a concentration of 0.4 mg / mL. It should be noted that when the polymer matrix is ​​aramid nanofibers, the weight proportions specified in the above raw material components correspond to their theoretical dry weight (i.e., the mass of solids excluding the mass of solvent), and the ethanol in the dispersion acts as a diluent.

[0021] In this paper, the two-dimensional sheet aluminum powder is a conventional chemical raw material that can be obtained commercially; preferably, the average outer diameter of the selected two-dimensional sheet aluminum powder is 10~100 μm and the average sheet thickness is in the nanometer range (e.g., 100~500 nm).

[0022] In this paper, the polydopamine-coated modified two-dimensional flake aluminum powder is prepared by dispersing the two-dimensional flake aluminum powder in a solution containing dopamine and then subjecting it to an oxidative self-polymerization reaction for 2.5–3.5 h. The polydopamine (PDA) coating is controllable by controlling the oxidative self-polymerization reaction time. Based on variable comparison experiments, further increasing the oxidative self-polymerization reaction time may lead to the formation of a significant series thermal resistance layer at the aluminum powder overlap due to an excessively thick coating layer.

[0023] It should be noted that the specific process for coating and modifying two-dimensional sheet aluminum powder with polydopamine can refer to the conventional polydopamine oxidative self-polymerization method in this field. However, it should be emphasized that the influence of the degree of polydopamine coating on the thermal conductivity of such highly filled systems has not been disclosed in the prior art. This invention achieves a balance between interfacial compatibility and thermal conductivity by optimizing and controlling the oxidative self-polymerization reaction time.

[0024] To better illustrate the present invention and provide a technical solution for reference, the preparation method of the polydopamine-coated modified two-dimensional flake aluminum powder includes the following steps:

[0025] Two-dimensional sheet aluminum powder was dispersed in deionized water, and dopamine hydrochloride and Tris buffer were added. Under stirring conditions, the mixture underwent an oxidative self-polymerization reaction for 2.5 to 3.5 hours. After the reaction time was reached, the mixture was separated, washed, and dried to obtain polydopamine-coated modified two-dimensional sheet aluminum powder.

[0026] Specifically, the amount of the two-dimensional flake aluminum powder added per 100 mL of deionized water is 1.5~2.5 g, the amount of dopamine hydrochloride added is 0.08~0.15 g, and the concentration of the Tris buffer is 1~1.1 mol / L with an added amount of 0.5~0.8 mL.

[0027] In this document, the eutectic gallium-indium alloy (EGaIn) may be commercially available or prepared according to methods known in the art. Preferably, the mass fraction of Ga in the selected eutectic gallium-indium alloy is 75%~76%, and the mass fraction of In is 24%~25%.

[0028] In one of the technical solutions, the modified eutectic gallium indium liquid metal microdroplets are prepared by dispersing a eutectic gallium indium alloy and a silane coupling agent in a solvent and then performing surface coordination modification, wherein the silane coupling agent is KH590 silane coupling agent (γ-mercaptopropyltrimethoxysilane).

[0029] By using KH590 silane coupling agent to perform surface coordination modification on eutectic gallium-indium alloy, the thiol group (-SH) at one end of the KH590 molecule has a strong coordination affinity for gallium and indium, and can coordinate with Ga and In ions in the native oxide layer (Ga2O3 / In2O3) on the surface of the eutectic gallium-indium alloy microdroplet to form stable Ga-S / In-S bonds, thereby firmly anchoring to the microdroplet surface in a self-assembly manner; at this time, the methoxysilane group (-Si(OCH3)3) at the other end of the KH590 molecule extends outward and remains intact. Furthermore, when the surface of the one-dimensional thermally conductive carbon-based filler has hydroxyl groups, when the modified eutectic gallium-indium liquid metal microdroplets are mixed and dispersed with the one-dimensional thermally conductive carbon-based filler, the outward-facing methoxysilane groups hydrolyze to form silanol (-Si(OH)3), which then undergoes a dehydration condensation reaction with the hydroxyl groups on the surface of the carbon-based filler to form stable Si-OC covalent bonds, thereby constructing a molecular-level interfacial bridge between the eutectic gallium-indium liquid metal microdroplets and the one-dimensional thermally conductive carbon-based filler. This invention utilizes the above mechanism to enable the liquid metal microdroplets to be stably dispersed in the matrix without agglomeration or leakage, and to form a low thermal resistance interface with the two-dimensional sheet-like aluminum powder and the one-dimensional thermally conductive carbon-based filler.

[0030] To better illustrate the present invention and provide a technical solution for reference, the modified eutectic gallium-indium liquid metal microdroplets are prepared by the following steps:

[0031] Eutectic gallium-indium alloy and KH590 silane coupling agent were dispersed in anhydrous ethanol. The eutectic gallium-indium alloy was dispersed into eutectic gallium-indium alloy microdroplets by ultrasonic treatment. At the same time, the mercapto end of KH590 silane coupling agent was coordinated and anchored with Ga and In ions in the oxide layer on the surface of the eutectic gallium-indium alloy microdroplets, thus obtaining modified eutectic gallium-indium liquid metal microdroplets dispersed in anhydrous ethanol.

[0032] In this process, the amount of the eutectic gallium-indium alloy added is 0.9~1.2 g per 100 mL of anhydrous ethanol, and the amount of the KH590 silane coupling agent added is 0.1~0.2 g. For ease of description, the modified eutectic gallium-indium liquid metal microdroplets prepared by this technical solution are designated as EGaIn@KH590. It should be noted that no deionized water is added during this modification process to avoid premature hydrolysis and self-condensation of the methoxysilane groups of KH590, which are retained until they are combined with one-dimensional thermally conductive carbon fillers before hydrolysis and condensation. The weight percentages of the modified eutectic gallium-indium liquid metal microdroplets in the above raw material components correspond to their converted theoretical dry weight (i.e., the mass of solids excluding the mass of solvent), and ethanol is used as a diluent.

[0033] In this paper, the one-dimensional thermally conductive carbon filler is a conventional carbon filler with thermal conductivity in the art, such as any one of carbon nanotubes, carbon fibers, carbon nanofibers, and graphene nanoribbons.

[0034] In one preferred embodiment, the one-dimensional thermally conductive carbon filler is a hydroxylated multi-walled carbon nanotube (MWCNTs-OH). MWCNTs possess a high aspect ratio and high intrinsic thermal conductivity, allowing them to interweave and overlap between two-dimensional sheet-like aluminum powder layers and between modified eutectic gallium indium liquid metal droplets, bridging and constructing one-dimensional secondary thermally conductive pathways and significantly increasing the thermally conductive network density. Furthermore, their abundant surface hydroxyl groups can form hydrogen bond networks with the catechol / amine groups on the surface of the polydopamine-coated modified two-dimensional sheet-like aluminum powder, the surface groups of the modified eutectic gallium indium liquid metal droplets, and the amide bonds on the surface of aramid nanofibers, improving the interfacial compatibility between the carbon nanotubes and various phases and reducing interfacial phonon scattering.

[0035] In one technical solution, in addition to the described raw materials, other additives commonly used in polymer-based thermally conductive composite materials may be included to further extend the product's functionality, assist in processing, or enhance its performance. The specific selection of these other additives can be referenced by those skilled in the art based on existing technology or literature, such as diluents, antioxidants, lubricants, heat stabilizers, and plasticizers. It should be noted that the raw materials may or may not include other additives commonly used in polymer-based thermally conductive composite materials.

[0036] To better illustrate the present invention and provide a reference technical solution, the raw materials further include a diluent, which is preferably anhydrous ethanol. It can be the aramid nanofiber / ethanol dispersion described in the above technical solution, the anhydrous ethanol already contained in the modified eutectic gallium indium liquid metal microdroplets dispersed in anhydrous ethanol, or additional anhydrous ethanol, preferably 60 to 80 parts of anhydrous ethanol.

[0037] Typically, the preparation method of the polymer-based thermally conductive composite material based on liquid metal interface bridging and multidimensional filler synergy involves mixing and dispersing each raw material component uniformly in a solvent, removing the solvent to form a film, and then hot-pressing it to obtain the final product. The solvent is preferably anhydrous ethanol and water, and the amount used is determined to meet the requirements for stable dispersion of each component and wet film formation.

[0038] In one technical solution, the hot pressing treatment is carried out at 180~220 ℃ and 10~12 MPa for 3~6 h.

[0039] One of the inventive points of this invention is the use of two-dimensional sheet-like aluminum powder with controllable polydopamine (PDA) coating as a highly filled thermally conductive filler, and the optimization window for the degree of polydopamine coating and the control mechanism of its thermal resistance layer in the highly filled system.

[0040] This invention, through systematic comparative experiments, reveals that in filler systems with total filler volume fractions as high as 65 vol% and 73.64 vol%, the degree of polydopamine coating on flake aluminum powder (with the coating layer thickness controlled by the oxidation self-polymerization reaction time) exhibits a non-monotonic effect on the thermal conductivity of the composite material, first increasing and then decreasing, with a significant optimal window (approximately 3 hours). This mechanism can be explained by the bidirectional competition between "interfacial compatibility benefits" and "low thermal resistance cost of the thermally conductive layer."

[0041] (a) The interface enhancement mechanism of moderate coating. A dense Al2O3 oxide layer exists on the surface of the flake aluminum powder, and there is a significant mismatch between the modulus and vibrational density between metallic aluminum and the polymer matrix, resulting in strong phonon scattering at the aluminum powder-matrix and aluminum powder-aluminum powder interfaces. The polydopamine layer, rich in catechol and amine groups, improves the dispersion of aluminum powder in the matrix and eliminates interfacial gaps between aluminum powder and the matrix through strong adhesion and hydrogen bonding. Furthermore, it forms a flexible phonon coupling transition layer between aluminum powder and the matrix, aluminum powder and liquid metal, and aluminum powder and one-dimensional thermally conductive carbon filler, mitigating modulus abrupt changes at the interface and suppressing phonon interfacial scattering, thereby reducing interfacial thermal resistance. Publicly available research indicates that the thickness of the polydopamine coating layer formed by the oxidative self-polymerization of dopamine increases with reaction time, typically increasing from several nanometers to hundreds of nanometers within several hours to 24 hours. However, the interfacial reinforcement effect of polydopamine competes with its own thermal insulation effect. Therefore, it is speculated that the thermal conductivity of the composite material is optimal when the coating degree is appropriate. However, whether an optimal value exists is directly related to the composite material system itself, and currently there is no systematic study that can predict the optimal coating degree. This invention focuses on aluminum-based filler composite material systems with ultra-high filler ratios and explores the oxidative self-polymerization reaction time of polydopamine through actual comparative experiments.

[0042] (b) The thermal resistance mechanism of over-coating. Polydopamine is an amorphous polymer with extremely low intrinsic thermal conductivity (less than 1 W / m·K, far lower than that of metallic aluminum). When the coating time is too long, the continuously thickening polydopamine layer forms a continuous low thermal conductivity coating shell on the aluminum powder surface. Heat must pass through this low thermal conductivity layer twice when crossing the aluminum powder-aluminum powder or aluminum powder-liquid metal interface. The polydopamine layer changes from an "interfacial compatibility medium" to a "thermal resistance barrier" connected in series on the thermal conduction path. Especially in high-filler systems (filler volume fraction > 65%), the sheet-like aluminum powders have largely overlapped with each other. The dominant limiting factor of the composite material's thermal conductivity changes from the filler-matrix interface thermal resistance to the filler-filler contact thermal resistance. At the same time, the excessively thick polydopamine layer located at the aluminum powder overlap joints is exactly on the main thermal conduction path, and its thermal resistance is further amplified. In addition, the excessively thick coating layer also occupies the effective contact area for direct bridging between the liquid metal and the aluminum powder surface, weakening the filling and welding effect of the liquid metal.

[0043] (c) Quantitative determination of the optimal window. In this invention, the effect of the reaction time (0.5 h, 1 h, 2 h, 3 h, 4 h, 6 h, 8 h) of polydopamine oxidative self-polymerization on the in-plane thermal conductivity of the composite material was systematically investigated in two high-filling systems: 65 vol% and 73.64 vol%. In the 73.64 vol% system, the thermal conductivity increased from approximately 18.5 W / m·K at 0.5 h to approximately 31.2 W / m·K (peak) at 3 h, and then decreased sharply to approximately 17.3 W / m·K at 4 h, and further decreased to approximately 11.9 W / m·K at 8 h. In the 65 vol% system, the thermal conductivity increased from approximately 16.0 W / m·K at 0.5 h to approximately 26.0 W / m·K (peak) at 3 h, and then gradually decreased to approximately 16.0 W / m·K at 8 h. Both curves exhibit a single-peak characteristic of first rising and then falling, with the peak value corresponding to an oxidative self-polymerization reaction time of approximately 3 hours. This indicates that the 3-hour mark represents the optimal coating window shared by both highly filled systems with the same formulation: at this point, the polydopamine layer thickness is moderate, maximizing interfacial compatibility benefits while thermal resistance costs are not yet significantly apparent. Compared to the uncoated polydopamine system with the same formulation and filling rate (73.64 vol%, approximately 27.2 W / m·K), the thermal conductivity of the 3-hour coated system (approximately 31.2 W / m·K) is increased by about 14%, and aluminum powder dispersibility and composite mechanical properties are improved simultaneously. However, after the coating time exceeds 4 hours, the thermal conductivity of the composite system is actually lower than that of the uncoated system, verifying the negative effects of an excessively thick polydopamine thermal resistance layer. These quantitative findings provide a clear process window for the precise application of polydopamine biomimetic interface modification in highly filled thermally conductive composite materials.

[0044] Based on the above-mentioned preferred technical solutions, the inventive point of this invention is that when the modified eutectic gallium indium liquid metal microdroplets are selected as EGaIn@KH590 and the one-dimensional thermally conductive carbon filler is selected as MWCNTs-OH, a synergistic thermal conductivity enhancement mechanism is achieved at a specific ratio.

[0045] Through a series of comparative experiments, the inventors of this invention discovered that in a highly filled composite material system with two-dimensional sheet-like aluminum powder as the dominant thermal filler and aramid nanofibers as the matrix, a significant synergistic thermal conductivity effect can only be achieved when liquid metal microdroplets EGaIn@KH590 (zero-dimensional filler) modified with KH590 surface coordination and hydroxylated multi-walled carbon nanotubes (MWCNTs-OH, one-dimensional filler) are present simultaneously and mixed in a specific ratio, resulting in a substantial increase in the thermal conductivity of the composite material. The absence of either one, or the replacement of the liquid metal with other zero-dimensional rigid particles, fails to achieve the aforementioned effect. Based on the experimental results, the mechanism can be elucidated from the following aspects:

[0046] (a) The flexible filling and bridging effect of liquid metal on the "discontinuities" in the heat conduction network. In the composite system of sheet aluminum powder / polymer matrix, it is difficult for rigid sheet aluminum powder to overlap fully. The gaps between the sheets are filled by the low thermal conductivity polymer matrix (e.g., aramid nanofibers of about 0.2 W / m·K) or air micro-gaps (about 0.026 W / m·K). These low thermal conductivity areas are the "discontinuities" in the heat conduction network. The heat transfer channels are discontinuous, resulting in high interfacial thermal resistance and low pathway efficiency. EGaIn is liquid at room temperature, possessing both a metallic-grade thermal conductivity of approximately 27 W / m·K and excellent flowability. During vacuum filtration and hot pressing, EGaIn@KH590 can wet, penetrate, and fill the micron / nanoscale gaps between the flake aluminum powder and the aramid nanofiber skeleton, replacing the "breakpoints" originally occupied by the matrix or air with a metallic-grade thermally conductive phase. Under the pressure of hot pressing, the liquid metal droplets can also deform, extend, and fuse together, transforming the "point contact" between the fillers into "surface contact," forming continuous, almost gapless thermally conductive microchannels. This is something that rigid zero-dimensional particles (such as Al2O3 particles and spherical aluminum powder) cannot achieve—rigid particles cannot conformally fill irregular gaps under molding pressure; instead, they themselves introduce new solid-solid interfaces and phonon scattering centers. The comparative experiments of this invention confirm that, under the same 65 vol% filler ratio, the composite material with spherical Al2O3 particles or spherical aluminum powder replacing EGaIn@KH590 has a thermal conductivity (approximately 10 W / m·K) comparable to the system without any zero-dimensional filler, which is much lower than the synergistic system provided by this invention (approximately 26.0 W / m·K). This indicates that the conformal filling and flexible bridging capabilities brought about by the fluidity of liquid metal are necessary prerequisites for the establishment of this synergistic effect.

[0047] (b) Molecular-level anchoring effect of silane coordination modification on liquid metal interface. Unmodified EGaIn has a high surface tension (approximately 700 mN / m) and poor compatibility with polar matrix and solid filler. Although its amorphous Ga2O3 native oxide layer can maintain the droplet morphology and inhibit exudation, it also hinders the effective interfacial bonding between liquid metal and solid filler. Simple physical blending is prone to problems such as liquid metal agglomeration and exudation. The mercapto group at one end of the KH590 molecule has a strong coordination affinity for gallium and indium, which can coordinate with Ga and In ions in the oxide layer on the surface of liquid metal droplets to form Ga-S / In-S bonds and firmly anchor it to the droplet surface. The methoxysilane group at the other end extends outward and remains intact. During the mixing, dispersion and hot pressing process, it hydrolyzes into silanol and dehydrates and condenses with the hydroxyl groups on the surface of hydroxylated multi-walled carbon nanotubes to form Si-OC covalent bonds, thereby forming a molecular-level chemical bridge between liquid metal droplets and carbon nanotubes. After modification with KH590, the liquid metal droplets are stably dispersed in the matrix, do not agglomerate or seep out, and the interfacial thermal resistance between them and the solid phases is significantly reduced.

[0048] (c) Carbon nanotubes and liquid metal form a “node-connection” neural network structure, which greatly increases the density of the thermal conductivity network. When MWCNTs-OH is added alone, although carbon nanotubes can construct a one-dimensional thermal conductivity pathway, the interfacial thermal resistance between them and the sheet aluminum powder and the matrix is ​​large, and the thermal conductivity network density is insufficient, resulting in limited enhancement efficiency. When EGaIn@KH590 is added alone, although liquid metal droplets can fill the gaps and bridge the aluminum powder, the droplets are isolated from each other and lack secondary pathways to connect the droplets, so the heat transfer between the sheets and in the normal direction is still limited. When both are present in a specific ratio, during the mixing, dispersion, and molding process, the high aspect ratio MWCNTs-OH interweaves and overlaps between the sheet-like aluminum powder layers and chemically bonds to the liquid metal droplets, forming a "node-synapse" structure similar to a neural network: the liquid metal droplets act as nodes in the network, distributed in the voids of the aluminum powder and "welding" the surrounding aluminum sheets into a continuous phase; the carbon nanotubes act as synaptic fibers connecting the nodes, bridging adjacent liquid metal droplets and sheet-like aluminum powder, and connecting isolated liquid metal nodes into a network. This structure significantly increases the connectivity density of the heat conduction network, expanding the heat conduction pathway from planar transmission within the two-dimensional sheet-like aluminum powder layers to a point-line-plane coupled three-dimensional heat conduction network of "two-dimensional sheet-like aluminum powder in-plane conduction - zero-dimensional liquid metal void bridging - one-dimensional carbon nanotube interlayer connection".

[0049] The present invention has the following beneficial effects:

[0050] 1. This invention provides a polymer-based thermally conductive composite material based on liquid metal interface bridging and multidimensional filler synergistic construction and its preparation method. It reveals the influence law of the degree of polydopamine coating on the thermal conductivity of the composite material in a "promotion-resistance" bidirectional competition under high filling system, and clarifies the optimal oxidative self-polymerization reaction time window of about 3 hours. While improving interfacial compatibility, it avoids the negative effects of excessively thick polydopamine thermal resistance layer, and provides experimental basis and process reference for the application of polydopamine biomimetic interface modification in high filling thermally conductive composite materials.

[0051] 2. In a preferred embodiment of the present invention, by the flow filling and flexible bridging effect of modified eutectic gallium indium liquid metal microdroplets, combined with the interpenetrating and overlapping effect of the one-dimensional thermal conductive pathway of hydroxylated multi-walled carbon nanotubes, a synergistic effect is formed at a specific ratio. A point-line-surface coupled three-dimensional thermal conductive network of "two-dimensional sheet-like aluminum powder in-plane conduction - zero-dimensional liquid metal void bridging - one-dimensional carbon nanotube interlayer interpenetration" is constructed in the polymer matrix, which reduces the multiphase interface thermal resistance and makes the in-plane thermal conductivity of the composite material more than twice that of the system lacking any synergistic component.

[0052] 3. In a preferred embodiment of the present invention, modified eutectic gallium indium liquid metal microdroplets and hydroxylated multi-walled carbon nanotubes form a “node-synapse” neural network structure through synergistic action: the liquid metal microdroplets act as nodes to fill the voids in the sheet-like aluminum powder and “weld” the aluminum sheets into a continuous phase; the high aspect ratio carbon nanotubes act as synaptic fibers to bridge the isolated microdroplets and aluminum sheets, thus upgrading the heat conduction pathway from two-dimensional planar transmission to a point-line-plane coupled three-dimensional heat conduction network of “two-dimensional sheet-like aluminum powder in-plane conduction - zero-dimensional liquid metal void bridging - one-dimensional carbon nanotube interlayer connection”. The heat conduction network connectivity density is greatly increased, overcoming the defects of high interfacial thermal resistance of single filler, insufficient network density, or isolated nodes, and significantly improving the thermal conductivity of the composite material. Attached Figure Description

[0053] Figure 1 The graphs show the in-plane thermal conductivity comparisons of the samples prepared in Examples 1-3, Comparative Examples 1-2, and Comparative Examples 7-11 of this invention. In these graphs, Al corresponds to two-dimensional sheet aluminum powder as the raw material component, and Al@PDA corresponds to two-dimensional sheet aluminum powder coated with polydopamine.

[0054] Figure 2 The above are line graphs comparing the in-plane thermal conductivity of the samples prepared in Example 1 and Comparative Examples 12-17 of this invention.

[0055] Figure 3 This is a bar chart comparing the in-plane thermal conductivity of the samples prepared in Example 2 and Comparative Examples 3-6 of the present invention.

[0056] Figure 4 This is a scanning electron microscope image of the two-dimensional flake aluminum powder in Comparative Example 7 of the present invention.

[0057] Figure 5 This is a scanning electron microscope image of the two-dimensional flake aluminum powder coated and modified with polydopamine in Example 1 of the present invention.

[0058] Figure 6 These are cross-sectional scanning electron microscope images of the polymer-based thermally conductive composite material prepared in Example 1 of the present invention at different scales.

[0059] Figure 7 This is an EDS elemental distribution diagram of the polymer-based thermally conductive composite material prepared in Example 1 of the present invention. Detailed Implementation

[0060] To further understand the present invention, preferred embodiments are described below with reference to examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, and not for limiting the scope of the claims. Those skilled in the art can refer to the content of this document to appropriately improve the process parameters. In particular, it should be noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included within the scope of the present invention. The methods and applications of the present invention have been described through preferred embodiments, and those skilled in the art can obviously make modifications or appropriate changes and combinations to the methods and applications described herein without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention. Although it is believed that those skilled in the art will fully understand the following terms, the following definitions are set forth to help illustrate the subject matter disclosed in the present invention.

[0061] This invention provides a polymer-based thermally conductive composite material constructed synergistically from liquid metal interface bridging and multidimensional fillers. The raw materials comprise the following components by weight:

[0062] 40-70 parts of polymer matrix,

[0063] 120-160 parts of polydopamine-coated modified two-dimensional flake aluminum powder

[0064] 60-80 parts of modified eutectic gallium indium liquid metal microdroplets,

[0065] 7-12 parts of one-dimensional thermally conductive carbon-based filler;

[0066] The polydopamine-coated modified two-dimensional sheet aluminum powder is prepared by dispersing the two-dimensional sheet aluminum powder in a solution containing dopamine and then subjecting it to an oxidative self-polymerization reaction for 2.5 to 3.5 hours.

[0067] The modified eutectic gallium-indium liquid metal microdroplets are prepared by dispersing a eutectic gallium-indium alloy and a silane coupling agent in a solvent and then modifying the surface coordination.

[0068] In this document, the polymer matrix is ​​a conventional polymer material that is suitable for thermoforming in the art, such as either aramid nanofibers or cellulose nanofibers.

[0069] In one embodiment, the polymer matrix is ​​40 to 70 parts, for example 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, or any range or point value between them.

[0070] In one preferred embodiment, the polymer matrix is ​​aramid nanofibers, whose abundant amide bonds can form a hydrogen bond network with the polydopamine coating layer and the hydroxyl groups on the filler surface, which is beneficial for constructing a composite material skeleton with strong interfacial bonding. Typically, the aramid nanofibers can be prepared from aramid fibers using a deprotonation method.

[0071] To better illustrate the present invention and provide a specific embodiment, the polymer matrix is ​​aramid nanofibers. The preparation method of the aramid nanofibers is as follows: 1 g of aramid fiber, 1.5 g of KOH, and 20 ml of deionized water are added to 500 mL of dimethyl sulfoxide and mixed to obtain an ANF / DMSO dispersion. 100 mL of the ANF / DMSO dispersion is mixed with 200 mL of deionized water and stirred. Then, the mixture is vacuum filtered and washed to remove dimethyl sulfoxide and KOH, yielding an aramid nanofiber colloid. For convenient direct use, anhydrous ethanol can be added to prepare an aramid nanofiber / ethanol dispersion with a concentration of 0.4 mg / mL. It should be noted that when the polymer matrix is ​​aramid nanofibers, the weight proportions specified in the above raw material components correspond to their theoretical dry weight (i.e., the mass of solids excluding the mass of solvent), and the ethanol in the dispersion is used as a diluent.

[0072] In this document, the two-dimensional sheet aluminum powder is a conventional chemical raw material that can be obtained commercially; in one embodiment, the average outer diameter of the selected two-dimensional sheet aluminum powder is 10~100 μm and the average sheet thickness is in the nanometer range (e.g., 100~500 nm).

[0073] In one embodiment, the polydopamine-coated modified two-dimensional flake aluminum powder is 120 to 160 parts, for example 120 parts, 125 parts, 130 parts, 135 parts, 140 parts, 145 parts, 150 parts, 155 parts, 160 parts or any range or point value between them.

[0074] In this paper, the polydopamine-coated modified two-dimensional flake aluminum powder is prepared by dispersing the two-dimensional flake aluminum powder in a solution containing dopamine and then subjecting it to an oxidative self-polymerization reaction for 2.5–3.5 h. The polydopamine (PDA) coating is controllable by controlling the oxidative self-polymerization reaction time. Based on variable comparison experiments, further increasing the oxidative self-polymerization reaction time may lead to the formation of a significant series thermal resistance layer at the aluminum powder overlap due to an excessively thick coating layer.

[0075] It should be noted that the specific process for coating and modifying two-dimensional sheet aluminum powder with polydopamine can refer to the conventional polydopamine oxidative self-polymerization method in this field. However, it should be emphasized that the influence of the degree of polydopamine coating on the thermal conductivity of such highly filled systems has not been disclosed in the prior art. This invention achieves a balance between interfacial compatibility and thermal conductivity by optimizing and controlling the oxidative self-polymerization reaction time.

[0076] To better illustrate the present invention and provide a reference embodiment, the polydopamine-coated modified two-dimensional flake aluminum powder is prepared by the following steps:

[0077] Two-dimensional sheet aluminum powder was dispersed in deionized water, and dopamine hydrochloride and Tris buffer were added. Under stirring conditions, the mixture underwent an oxidative self-polymerization reaction for 2.5 to 3.5 hours. After the reaction time was reached, the mixture was separated, washed, and dried to obtain polydopamine-coated modified two-dimensional sheet aluminum powder.

[0078] Specifically, the amount of the two-dimensional flake aluminum powder added per 100 mL of deionized water is 1.5~2.5 g, the amount of dopamine hydrochloride added is 0.08~0.15 g, and the concentration of the Tris buffer is 1~1.1 mol / L with an added amount of 0.5~0.8 mL.

[0079] In this document, the eutectic gallium-indium alloy (EGaIn) may be commercially available or prepared according to methods known in the art. In one embodiment, the selected eutectic gallium-indium alloy contains 75% to 76% Ga by mass and 24% to 25% In by mass.

[0080] In one embodiment, the modified eutectic gallium indium liquid metal droplets are 60 to 80 parts, for example 60 parts, 65 parts, 70 parts, 75 parts, 80 parts or any range or point value between them.

[0081] In one embodiment, the modified eutectic gallium-indium liquid metal microdroplets are prepared by dispersing a eutectic gallium-indium alloy and a silane coupling agent in a solvent and then performing surface coordination modification, wherein the silane coupling agent is KH590 silane coupling agent (γ-mercaptopropyltrimethoxysilane).

[0082] By using KH590 silane coupling agent to perform surface coordination modification on eutectic gallium-indium alloy, the thiol group (-SH) at one end of the KH590 molecule has a strong coordination affinity for gallium and indium, and can coordinate with Ga and In ions in the native oxide layer (Ga2O3 / In2O3) on the surface of the eutectic gallium-indium alloy microdroplet to form stable Ga-S / In-S bonds, thereby firmly anchoring to the microdroplet surface in a self-assembly manner; at this time, the methoxysilane group (-Si(OCH3)3) at the other end of the KH590 molecule extends outward and remains intact. Furthermore, when the surface of the one-dimensional thermally conductive carbon-based filler has hydroxyl groups, when the modified eutectic gallium-indium liquid metal microdroplets are mixed and dispersed with the one-dimensional thermally conductive carbon-based filler, the outward-facing methoxysilane groups hydrolyze to form silanol (-Si(OH)3), which then undergoes a dehydration condensation reaction with the hydroxyl groups on the surface of the carbon-based filler to form stable Si-OC covalent bonds, thereby constructing a molecular-level interfacial bridge between the eutectic gallium-indium liquid metal microdroplets and the one-dimensional thermally conductive carbon-based filler. This invention utilizes the above mechanism to enable the liquid metal microdroplets to be stably dispersed in the matrix without agglomeration or leakage, and to form a low thermal resistance interface with the two-dimensional sheet-like aluminum powder and the one-dimensional thermally conductive carbon-based filler.

[0083] To better illustrate the present invention and provide an embodiment for reference, the modified eutectic gallium-indium liquid metal microdroplets are prepared by the following steps:

[0084] Eutectic gallium-indium alloy and KH590 silane coupling agent were dispersed in anhydrous ethanol. The eutectic gallium-indium alloy was dispersed into eutectic gallium-indium alloy microdroplets by ultrasonic treatment. At the same time, the mercapto end of KH590 silane coupling agent was coordinated and anchored with Ga and In ions in the oxide layer on the surface of the eutectic gallium-indium alloy microdroplets, thus obtaining modified eutectic gallium-indium liquid metal microdroplets dispersed in anhydrous ethanol.

[0085] In this embodiment, the amount of eutectic gallium-indium alloy added is 0.9~1.2 g per 100 mL of anhydrous ethanol, and the amount of KH590 silane coupling agent added is 0.1~0.2 g. For ease of description, the modified eutectic gallium-indium liquid metal microdroplets prepared in this embodiment are referred to as EGaIn@KH590. It should be noted that deionized water is not added during this modification process to avoid premature hydrolysis and self-condensation of the methoxysilane groups of KH590, so that they are retained until they are combined with one-dimensional thermally conductive carbon fillers before hydrolysis and condensation. The weight fractions of the modified eutectic gallium-indium liquid metal microdroplets in the above raw material components correspond to their theoretical dry weight (i.e., the mass of solids excluding the mass of solvent), and ethanol is used as a diluent.

[0086] In this document, the one-dimensional thermally conductive carbon filler is a conventional carbon filler with thermal conductivity in the art, and in one embodiment, it includes, for example, any one of carbon nanotubes, carbon fibers, carbon nanofibers, and graphene nanoribbons.

[0087] In one embodiment, the one-dimensional thermally conductive carbon filler is 7 to 12 parts, for example 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts or any range or point value between them.

[0088] In one preferred embodiment, the one-dimensional thermally conductive carbon filler is hydroxylated multi-walled carbon nanotubes (MWCNTs-OH). MWCNTs possess a high aspect ratio and high intrinsic thermal conductivity, allowing them to interweave and overlap between two-dimensional sheet-like aluminum powder layers and between modified eutectic gallium indium liquid metal droplets, bridging and constructing one-dimensional secondary thermally conductive pathways and significantly increasing the thermally conductive network density. Furthermore, their abundant surface hydroxyl groups can form hydrogen bond networks with the catechol / amine groups on the surface of the polydopamine-coated modified two-dimensional sheet-like aluminum powder, the surface groups of the modified eutectic gallium indium liquid metal droplets, and the amide bonds on the surface of aramid nanofibers, improving the interfacial compatibility between the carbon nanotubes and the various phases and reducing interfacial phonon scattering.

[0089] In one embodiment, in addition to the described raw materials, other additives conventionally used in polymer-based thermally conductive composite materials may be included to further extend the product's functionality / process aid / reinforcement. The specific selection of these other additives can be found by those skilled in the art based on existing technology or literature, and may include, for example, diluents, antioxidants, lubricants, heat stabilizers, and plasticizers. It should be noted that the raw materials may or may not include other additives conventionally used in polymer-based thermally conductive composite materials.

[0090] To better illustrate the present invention and provide an embodiment for reference, the raw materials further include a diluent, which is preferably anhydrous ethanol. The diluent may be the aramid nanofiber / ethanol dispersion described in the above embodiments, the anhydrous ethanol already contained in the modified eutectic gallium indium liquid metal microdroplets dispersed in anhydrous ethanol, or additional anhydrous ethanol, preferably 60 to 80 parts of anhydrous ethanol.

[0091] Typically, the preparation method of the polymer-based thermally conductive composite material based on liquid metal interface bridging and multidimensional filler synergy involves mixing and dispersing each raw material component uniformly in a solvent, removing the solvent to form a film, and then hot-pressing it to obtain the final product. In one embodiment, the solvent is preferably anhydrous ethanol and water, and the amount used is determined to meet the requirements of stable dispersion of each component and wet film formation.

[0092] In one embodiment, the hot pressing treatment is performed at 180~220 °C and 10~12 MPa for 3~6 h.

[0093] The present application will be further explained in detail below with reference to embodiments. However, those skilled in the art should understand that these embodiments are provided for illustrative purposes only and are not intended to limit the present application.

[0094] Example

[0095] The embodiments of this application will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be construed as limiting the scope of this application. Where specific conditions are not specified in the examples, conventional conditions or conditions recommended by the manufacturer shall apply. Where the manufacturers of reagents or instruments are not specified, they are all commercially available conventional products. This application should not be construed as being limited to the specific embodiments described.

[0096] 1. Raw materials

[0097] Two-dimensional flake aluminum powder (two-dimensional flakes, outer diameter 15 μm, average flake thickness 100~500 nm).

[0098] Eutectic gallium-indium alloy (EGaIn, Ga 75.5 wt%, In 24.5 wt%);

[0099] KH590 silane coupling agent (γ-mercaptopropyltrimethoxysilane).

[0100] Hydroxylated multi-walled carbon nanotubes (MWCNTs-OH, outer diameter 8~15 nm, length 5~30 μm, hydroxyl content 2~8 wt%).

[0101] 2. Preparation method

[0102] (1) Aramid nanofibers

[0103] An ANF / DMSO dispersion was prepared by mixing 1 g of aramid fiber, 1.5 g of KOH, and 20 mL of deionized water in 500 mL of dimethyl sulfoxide. 100 mL of the ANF / DMSO dispersion was then mixed with 200 mL of deionized water and stirred. The mixture was then vacuum filtered and washed to remove dimethyl sulfoxide and KOH, yielding an aramid nanofiber colloid. Finally, anhydrous ethanol was added to prepare an aramid nanofiber / ethanol dispersion with a concentration of 0.4 mg / mL.

[0104] (2) Polydopamine-coated modified two-dimensional flake aluminum powder

[0105] Two-dimensional sheet aluminum powder was dispersed in deionized water, and dopamine hydrochloride and Tris buffer were added. The mixture was subjected to oxidative self-polymerization reaction for 3 h under stirring. After the reaction time was reached, the mixture was vacuum filtered, and the precipitate was washed with deionized water at least 3 times. The product was then dried in a vacuum oven at 60 °C to obtain polydopamine-coated modified two-dimensional sheet aluminum powder.

[0106] Specifically, based on 100 mL of deionized water, the amount of the two-dimensional flake aluminum powder added is 2 g, the amount of dopamine hydrochloride added is 0.1 g, and the concentration of the Tris buffer is 1 mol / L with an added amount of 0.6 mL.

[0107] (3) Modified eutectic gallium indium liquid metal microdroplets

[0108] Eutectic gallium-indium alloy and KH590 silane coupling agent were dispersed in anhydrous ethanol. After ultrasonic treatment for 1 h, the eutectic gallium-indium alloy was dispersed into eutectic gallium-indium alloy microdroplets. At the same time, the mercapto end of KH590 silane coupling agent was coordinated and anchored with Ga and In ions in the oxide layer on the surface of the eutectic gallium-indium alloy microdroplets, thus obtaining modified eutectic gallium-indium liquid metal microdroplets dispersed in anhydrous ethanol.

[0109] Specifically, the amount of the eutectic gallium indium alloy added is 1 g per 100 mL of anhydrous ethanol, and the amount of the KH590 silane coupling agent added is 0.12 g.

[0110] Prepare the following raw material components according to parts by weight:

[0111] 40-70 parts of aramid nanofibers

[0112] 120-160 parts of polydopamine-coated modified two-dimensional flake aluminum powder

[0113] 60-80 parts of modified eutectic gallium indium liquid metal microdroplets,

[0114] 7-12 parts of hydroxylated multi-walled carbon nanotubes

[0115] 60-80 parts of anhydrous ethanol

[0116] 1 part deionized water;

[0117] The weight fraction of aramid nanofibers is the theoretical dry weight of the aramid nanofibers in the aramid nanofiber / ethanol dispersion prepared above.

[0118] The weight fraction of the modified eutectic gallium indium liquid metal microdroplets is the theoretical dry weight of the modified eutectic gallium indium liquid metal microdroplets dispersed in anhydrous ethanol as prepared above.

[0119] Each raw material component was ultrasonically stirred and dispersed in anhydrous ethanol at 100 W ultrasonic power for 1 h, then vacuum filtered to form a film, and hot-pressed at 200 ℃ and 10 MPa for 4 h to obtain the polymer-based thermally conductive composite material.

[0120] 3. Testing Methods

[0121] Thermal conductivity was measured using the laser flare method (LFA, Netzsch LFA 467), and was calculated from the product of thermal diffusivity, specific heat capacity and density. Thermal conductivity in both the in-plane and normal directions was tested.

[0122] The microstructure was observed using scanning electron microscopy (SEM) and transmission electron microscopy (TEM).

[0123] The chemical structure was analyzed using Fourier transform infrared spectroscopy (FTIR, Nicolet iS50).

[0124] Mechanical properties were determined using an electronic universal testing machine in accordance with ISO 527-3 standard.

[0125] Example 1

[0126] Example 1 describes the preparation of a polymer-based thermally conductive composite material according to the steps described in "2. Preparation Method" above, wherein the proportions of each raw material component are as follows:

[0127] 40 parts of aramid nanofibers

[0128] 160 parts of polydopamine-coated modified two-dimensional flake aluminum powder

[0129] 80 parts of modified eutectic gallium indium liquid metal microdroplets

[0130] 10 parts of hydroxylated multi-walled carbon nanotubes,

[0131] 80 parts of anhydrous ethanol

[0132] 1 part deionized water;

[0133] By volume fraction, in this embodiment, the polymer-based thermally conductive composite material contains approximately 56.63 vol% polydopamine-coated modified two-dimensional sheet aluminum powder, approximately 12.23 vol% modified eutectic gallium indium liquid metal microdroplets, and approximately 4.78 vol% hydroxylated multi-walled carbon nanotubes. Therefore, the total filler content is approximately 73.64 vol%, and aramid nanofibers account for approximately 26.36 vol%.

[0134] The polymer-based thermally conductive composite material prepared in this embodiment was used as a sample for testing, and its in-plane thermal conductivity was approximately 31.2 W / m·K.

[0135] Example 2

[0136] Example 2 describes the preparation of a polymer-based thermally conductive composite material according to the steps described in "2. Preparation Method" above, wherein the proportions of each raw material component are as follows:

[0137] 53.1 parts of aramid nanofibers

[0138] 142 parts of polydopamine-coated modified two-dimensional flake aluminum powder

[0139] 70 parts of modified eutectic gallium-indium liquid metal microdroplets,

[0140] Nine portions of hydroxylated multi-walled carbon nanotubes,

[0141] 70 parts of anhydrous ethanol

[0142] 1 part deionized water;

[0143] The total filler content in the polymer-based thermally conductive composite material of this embodiment is approximately 65 vol by volume fraction.

[0144] The polymer-based thermally conductive composite material prepared in this embodiment was used as a sample for testing, and its in-plane thermal conductivity was approximately 26.0 W / m·K.

[0145] Example 3

[0146] Example 3 describes the preparation of a polymer-based thermally conductive composite material according to the steps described in "2. Preparation Method" above, wherein the proportions of each raw material component are as follows:

[0147] Aramid nanofibers, 68.3 parts

[0148] 120 parts of polydopamine-coated modified two-dimensional flake aluminum powder

[0149] 60 parts of modified eutectic gallium indium liquid metal microdroplets,

[0150] 7.5 parts of hydroxylated multi-walled carbon nanotubes

[0151] 60 parts of anhydrous ethanol

[0152] 1 part deionized water;

[0153] The total filler content in the polymer-based thermally conductive composite material of this embodiment is approximately 55 vol by volume fraction.

[0154] The polymer-based thermally conductive composite material prepared in this embodiment was used as a sample for testing, and its in-plane thermal conductivity was approximately 23.4 W / m·K.

[0155] Comparative Example 1

[0156] Comparative Example 1 shows a polymer-based thermally conductive composite material prepared according to the steps in "2. Preparation Method" above, wherein the proportions of each raw material component are as follows:

[0157] 78.9 parts of aramid nanofibers

[0158] 61 parts of polydopamine-coated modified two-dimensional flake aluminum powder,

[0159] 30 parts of modified eutectic gallium indium liquid metal microdroplets,

[0160] Four portions of hydroxylated multi-walled carbon nanotubes.

[0161] 40 parts of anhydrous ethanol

[0162] 1 part deionized water;

[0163] The total filler content in the polymer-based thermally conductive composite material of this embodiment is approximately 35 vol by volume fraction.

[0164] The polymer-based thermally conductive composite material prepared in this comparative example was used as a sample for testing, and its in-plane thermal conductivity was approximately 9.6 W / m·K.

[0165] Comparative Example 2

[0166] Comparative Example 2 shows a polymer-based thermally conductive composite material prepared according to the steps described in "2. Preparation Method" above, wherein the proportions of each raw material component are as follows:

[0167] 77.4 parts of aramid nanofibers

[0168] 20 parts of polydopamine-coated modified two-dimensional flake aluminum powder

[0169] 9.6 parts of modified eutectic gallium indium liquid metal microdroplets,

[0170] 1.2 parts of hydroxylated multi-walled carbon nanotubes,

[0171] 40 parts of anhydrous ethanol

[0172] 1 part deionized water;

[0173] The total filler content in the polymer-based thermally conductive composite material of this embodiment is approximately 15 vol by volume fraction.

[0174] The polymer-based thermally conductive composite material prepared in this comparative example was used as a sample for testing, and its in-plane thermal conductivity was approximately 8.4 W / m·K.

[0175] Comparative Example 3

[0176] Comparative Example 3 shows a polymer-based thermally conductive composite material prepared according to the steps described in "2. Preparation Method" above, wherein the proportions of each raw material component are as follows:

[0177] 53.1 parts of aramid nanofibers

[0178] 142 parts of polydopamine-coated modified two-dimensional flake aluminum powder

[0179] 103 parts of modified eutectic gallium-indium liquid metal microdroplets,

[0180] 70 parts of anhydrous ethanol

[0181] 1 part deionized water;

[0182] The polymer-based thermally conductive composite material prepared in this comparative example was used as a sample for testing, and its in-plane thermal conductivity was approximately 11.9 W / m·K. This indicates that when the raw material components do not contain hydroxylated multi-walled carbon nanotubes, the thermal conductivity network connectivity density is insufficient when liquid metal bridging is used alone without a one-dimensional secondary thermal conduction pathway.

[0183] It should be noted that the amount of modified eutectic gallium indium liquid metal droplets added is to maintain the same total filler volume fraction as in Example 2.

[0184] Comparative Example 4

[0185] Comparative Example 4 shows a polymer-based thermally conductive composite material prepared according to the steps in "2. Preparation Method" above, wherein the proportions of each raw material component are as follows:

[0186] 53.1 parts of aramid nanofibers

[0187] 142 parts of polydopamine-coated modified two-dimensional flake aluminum powder

[0188] 31 portions of hydroxylated multi-walled carbon nanotubes,

[0189] 70 parts of anhydrous ethanol;

[0190] The polymer-based thermally conductive composite material prepared in this comparative example was used as a sample for testing, and its in-plane thermal conductivity was approximately 13.9 W / m·K. This indicates that when the raw material composition does not contain modified eutectic gallium indium liquid metal droplets, and carbon nanotubes are used alone without the conformal filling and flexible bridging of liquid metal, the voids between the fillers are still occupied by the low thermal conductivity phase, and the synergistic effect cannot be established.

[0191] It should be noted that the amount of hydroxylated multi-walled carbon nanotubes added is to maintain the same total filler volume fraction as in Example 2.

[0192] Comparative Example 5

[0193] Comparative Example 5 shows a polymer-based thermally conductive composite material prepared according to the steps described in "2. Preparation Method" above, wherein the proportions of each raw material component are as follows:

[0194] 53.1 parts of aramid nanofibers

[0195] 142 parts of polydopamine-coated modified two-dimensional flake aluminum powder

[0196] 44 parts of spherical Al2O3 particles

[0197] Nine portions of hydroxylated multi-walled carbon nanotubes,

[0198] 70 parts of anhydrous ethanol;

[0199] The polymer-based thermally conductive composite material prepared in this comparative example was tested as a sample. Its in-plane thermal conductivity was approximately 9.6 W / m·K, comparable to that of the sample in Comparative Example 4, but significantly lower than that in Example 2 (approximately 26.0 W / m·K). This indicates that after replacing the modified eutectic gallium indium liquid metal droplets with spherical Al2O3 particles, the rigid zero-dimensional particles cannot conformally fill the gaps between the sheet-like aluminum powder and the matrix, and therefore cannot replace the liquid metal in providing a flexible bridging effect.

[0200] It should be noted that the amount of spherical Al2O3 particles added is to maintain the same total filler volume fraction as in Example 2.

[0201] Comparative Example 6

[0202] Comparative Example 6 shows a polymer-based thermally conductive composite material prepared according to the steps described in "2. Preparation Method" above, wherein the proportions of each raw material component are as follows:

[0203] 53.1 parts of aramid nanofibers

[0204] 142 parts of polydopamine-coated modified two-dimensional flake aluminum powder

[0205] 31 parts of spherical aluminum powder

[0206] Nine portions of hydroxylated multi-walled carbon nanotubes,

[0207] 70 parts of anhydrous ethanol;

[0208] The polymer-based thermally conductive composite material prepared in this comparative example was tested as a sample. Its in-plane thermal conductivity was approximately 10.4 W / m·K, comparable to that of the sample in Comparative Example 4, but significantly lower than that in Example 2 (approximately 26.0 W / m·K). This indicates that although the intrinsic thermal conductivity of the spherical aluminum powder is higher, it cannot deform to fill the voids during the molding process after replacing the modified eutectic gallium indium liquid metal droplets with spherical aluminum powder. Instead, it introduces a new solid-solid interface, further demonstrating that the fluidity of the liquid metal is a necessary condition for the synergistic system of this invention.

[0209] It should be noted that the amount of spherical aluminum powder added is to maintain the same total filler volume fraction as in Example 2.

[0210] Similar control experiments conducted using Example 1 as the control condition also yielded the same conclusion.

[0211] Comparative Example 7

[0212] Comparative Example 7 shows a polymer-based thermally conductive composite material prepared according to the steps described in "2. Preparation Method" above, wherein the proportions of each raw material component are as follows:

[0213] 40 parts of aramid nanofibers

[0214] 160 parts of two-dimensional flake aluminum powder

[0215] 80 parts of modified eutectic gallium indium liquid metal microdroplets

[0216] 10 parts of hydroxylated multi-walled carbon nanotubes,

[0217] 80 parts of anhydrous ethanol

[0218] 1 part deionized water;

[0219] The polymer-based thermally conductive composite material prepared in this comparative example was used as a sample for testing, and its in-plane thermal conductivity was approximately 27.2 W / m·K. Compared with Example 1 (approximately 31.2 W / m·K), this demonstrates that moderate polydopamine coating can further improve thermal conductivity by improving interfacial compatibility.

[0220] Comparative Example 8

[0221] Comparative Example 8 shows a polymer-based thermally conductive composite material prepared according to the steps described in "2. Preparation Method" above, wherein the proportions of each raw material component are as follows:

[0222] 53.1 parts of aramid nanofibers

[0223] 142 parts of two-dimensional flake aluminum powder

[0224] 70 parts of modified eutectic gallium-indium liquid metal microdroplets,

[0225] Nine portions of hydroxylated multi-walled carbon nanotubes,

[0226] 70 parts of anhydrous ethanol

[0227] 1 part deionized water;

[0228] The polymer-based thermally conductive composite material prepared in this comparative example was used as a sample for testing, and its in-plane thermal conductivity was approximately 22.2 W / m·K.

[0229] Comparative Example 9

[0230] Comparative Example 9 shows a polymer-based thermally conductive composite material prepared according to the steps described in "2. Preparation Method" above, wherein the proportions of each raw material component are as follows:

[0231] Aramid nanofibers, 68.3 parts

[0232] 120 parts of two-dimensional flake aluminum powder

[0233] 60 parts of modified eutectic gallium indium liquid metal microdroplets,

[0234] 7.5 parts of hydroxylated multi-walled carbon nanotubes

[0235] 60 parts of anhydrous ethanol

[0236] 1 part deionized water;

[0237] The polymer-based thermally conductive composite material prepared in this comparative example was used as a sample for testing, and its in-plane thermal conductivity was approximately 15.6 W / m·K.

[0238] Comparative Example 10

[0239] Comparative Example 10 is a polymer-based thermally conductive composite material prepared according to the steps in "2. Preparation Method" above, wherein the proportions of each raw material component are as follows:

[0240] 78.9 parts of aramid nanofibers

[0241] 61 parts of two-dimensional flake aluminum powder

[0242] 30 parts of modified eutectic gallium indium liquid metal microdroplets,

[0243] Four portions of hydroxylated multi-walled carbon nanotubes.

[0244] 40 parts of anhydrous ethanol

[0245] 1 part deionized water;

[0246] The polymer-based thermally conductive composite material prepared in this comparative example was used as a sample for testing, and its in-plane thermal conductivity was approximately 8.7 W / m·K.

[0247] Comparative Example 11

[0248] Comparative Example 11 is a polymer-based thermally conductive composite material prepared according to the steps in "2. Preparation Method" above, wherein the proportions of each raw material component are as follows:

[0249] 77.4 parts of aramid nanofibers

[0250] 20 parts of two-dimensional flake aluminum powder

[0251] 9.6 parts of modified eutectic gallium indium liquid metal microdroplets,

[0252] 1.2 parts of hydroxylated multi-walled carbon nanotubes,

[0253] 40 parts of anhydrous ethanol

[0254] 1 part deionized water;

[0255] The polymer-based thermally conductive composite material prepared in this comparative example was used as a sample for testing, and its in-plane thermal conductivity was approximately 6.1 W / m·K.

[0256] Comparative Example 12

[0257] The raw material composition of Comparative Example 12 was the same as that of Example 1, but the oxidative self-polymerization reaction time in the preparation of polydopamine-coated modified two-dimensional sheet aluminum powder was 0.5 h.

[0258] The polymer-based thermally conductive composite material prepared in this comparative example was used as a sample for testing, and its in-plane thermal conductivity was approximately 18.5 W / m·K. Due to the short coating time, the PDA layer did not fully cover the aluminum powder surface, resulting in limited improvement in interfacial compatibility.

[0259] Comparative Example 13

[0260] The raw material composition of Comparative Example 13 was the same as that of Example 1, but the oxidative self-polymerization reaction time in the preparation of polydopamine-coated modified two-dimensional sheet aluminum powder was 1 h.

[0261] The polymer-based thermally conductive composite material prepared in this comparative example was used as a sample for testing, and its in-plane thermal conductivity was approximately 24.6 W / m·K.

[0262] Comparative Example 14

[0263] The raw material composition of Comparative Example 14 was the same as that of Example 1, but the oxidative self-polymerization reaction time in the preparation of polydopamine-coated modified two-dimensional sheet aluminum powder was 2 h.

[0264] The polymer-based thermally conductive composite material prepared in this comparative example was used as a sample for testing, and its in-plane thermal conductivity was approximately 25.1 W / m·K.

[0265] Comparative Example 15

[0266] The raw material composition of Comparative Example 15 was the same as that of Example 1, but the oxidative self-polymerization reaction time in the preparation of polydopamine-coated modified two-dimensional sheet aluminum powder was 4 h.

[0267] The polymer-based thermally conductive composite material prepared in this comparative example was used as a sample for testing, and its in-plane thermal conductivity was approximately 17.3 W / m·K. This indicates that when the coating time is too long, an excessively thick polydopamine layer forms a low thermal conductivity thermal resistance layer at the aluminum powder overlap, and its additional thermal resistance exceeds the benefit of interface improvement.

[0268] Comparative Example 16

[0269] The raw material composition of Comparative Example 16 was the same as that of Example 1, but the oxidative self-polymerization reaction time in the preparation of polydopamine-coated modified two-dimensional sheet aluminum powder was 6 h.

[0270] The polymer-based thermally conductive composite material prepared in this comparative example was used as a sample for testing, and its in-plane thermal conductivity was approximately 16.1 W / m·K.

[0271] Comparative Example 17

[0272] The raw material composition of Comparative Example 17 was the same as that of Example 1, but the oxidative self-polymerization reaction time was 8 h during the preparation of polydopamine-coated modified two-dimensional sheet aluminum powder.

[0273] The polymer-based thermally conductive composite material prepared in this comparative example was used as a sample for testing, and its in-plane thermal conductivity was approximately 11.9 W / m·K.

[0274] like Figure 1 The figure shows a comparative graph of the in-plane thermal conductivity of the samples prepared in Examples 1-3, Comparative Examples 1-2, and Comparative Examples 7-11 of this invention. The graph reveals that as the total filler volume ratio increases, the interfacial enhancement mechanism of polydopamine coating in the high-filler system is revealed.

[0275] like Figure 2 The figure shows a comparative linear graph of the in-plane thermal conductivity of the samples prepared in Example 1 and Comparative Examples 12-17 of this invention. As can be seen from the figure, the degree of coating of the flake aluminum powder by polydopamine (the coating thickness is controlled by the oxidation self-polymerization reaction time) has a non-monotonic effect on the thermal conductivity of the composite material, which first increases and then decreases, and there is a significant optimal window (about 3 h).

[0276] like Figure 3 The figure shows a bar chart comparing the in-plane thermal conductivity of the samples prepared in Example 2 and Comparative Examples 3-6 of this invention. It can be seen from the figure that the conformal filling effect brought about by the fluidity of the modified eutectic gallium-indium liquid metal microdroplets and the flexible bridging ability of the hydroxylated multi-walled carbon nanotubes are necessary prerequisites for the synergistic effect to occur.

[0277] like Figure 4 As shown, a scanning electron microscope image of the two-dimensional flake aluminum powder in Comparative Example 7 of the present invention is displayed.

[0278] like Figure 5 The image shows a scanning electron microscope image of two-dimensional flake aluminum powder coated with polydopamine according to Example 1 of the present invention. The image clearly shows a significant modification and coating effect.

[0279] like Figure 6 The images show cross-sectional scanning electron microscope (SEM) images of the polymer-based thermally conductive composite material prepared in Example 1 of this invention at different scales. As can be seen from the images, the fillers are intertwined to form a highly efficient three-dimensional thermally conductive network.

[0280] like Figure 7 The figure shows the EDS elemental distribution map of the polymer-based thermally conductive composite material prepared in Example 1 of the present invention. It can be seen from the figure that the polydopamine coating modification and the synergistic construction of materials in each dimension create a continuous thermally conductive pathway.

[0281] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A polymer-based thermally conductive composite material constructed based on liquid metal interface bridging and multidimensional filler synergy, characterized in that... Its raw materials, based on parts by weight, include the following components: 40-70 parts of polymer matrix, 120-160 parts of polydopamine-coated modified two-dimensional flake aluminum powder 60-80 parts of modified eutectic gallium indium liquid metal microdroplets, 7-12 parts of one-dimensional thermally conductive carbon-based filler; The polydopamine-coated modified two-dimensional sheet aluminum powder is prepared by dispersing the two-dimensional sheet aluminum powder in a solution containing dopamine and then subjecting it to an oxidative self-polymerization reaction for 2.5 to 3.5 hours. The modified eutectic gallium-indium liquid metal microdroplets are prepared by dispersing a eutectic gallium-indium alloy and a silane coupling agent in a solvent and then modifying the surface coordination.

2. The polymer-based thermally conductive composite material according to claim 1, characterized in that: The polymer matrix includes either aramid nanofibers or cellulose nanofibers.

3. The polymer-based thermally conductive composite material according to claim 1, characterized in that: The polydopamine-coated modified two-dimensional flake aluminum powder is prepared by the following steps: Two-dimensional sheet aluminum powder was dispersed in deionized water, and dopamine hydrochloride and Tris buffer were added. Under stirring conditions, the mixture underwent an oxidative self-polymerization reaction for 2.5 to 3.5 hours. After the reaction time was reached, the mixture was separated, washed, and dried to obtain polydopamine-coated modified two-dimensional sheet aluminum powder. Specifically, the amount of the two-dimensional flake aluminum powder added per 100 mL of deionized water is 1.5~2.5 g, the amount of dopamine hydrochloride added is 0.08~0.15 g, and the concentration of the Tris buffer is 1~1.1 mol / L with an added amount of 0.5~0.8 mL.

4. The polymer-based thermally conductive composite material according to claim 1, characterized in that: The silane coupling agent is KH590 silane coupling agent.

5. The polymer-based thermally conductive composite material according to claim 1, characterized in that: The modified eutectic gallium-indium liquid metal microdroplets are prepared by the following steps: Eutectic gallium-indium alloy and KH590 silane coupling agent were dispersed in anhydrous ethanol. The eutectic gallium-indium alloy was dispersed into eutectic gallium-indium alloy microdroplets by ultrasonic treatment. At the same time, the mercapto end of KH590 silane coupling agent was coordinated and anchored with Ga and In ions in the oxide layer on the surface of the eutectic gallium-indium alloy microdroplets, thus obtaining modified eutectic gallium-indium liquid metal microdroplets dispersed in anhydrous ethanol. Specifically, the amount of the eutectic gallium-indium alloy added is 0.9~1.2 g per 100 mL of anhydrous ethanol, and the amount of the KH590 silane coupling agent added is 0.1~0.2 g.

6. The polymer-based thermally conductive composite material according to claim 1, characterized in that: The one-dimensional thermally conductive carbon-based filler includes any one of carbon nanotubes, carbon fibers, carbon nanofibers, and graphene nanoribbons.

7. The polymer-based thermally conductive composite material according to claim 1, characterized in that: The one-dimensional thermally conductive carbon-based filler is a hydroxylated multi-walled carbon nanotube.

8. The polymer-based thermally conductive composite material according to claim 1, characterized in that: The preparation method of the polymer-based thermally conductive composite material is to mix and disperse each raw material component evenly in a solvent, remove the solvent to form a film, and then perform hot pressing treatment to obtain the film; the solvent includes water.